2018
DOI: 10.1111/jphd.12266
|View full text |Cite
|
Sign up to set email alerts
|

Association of oral health literacy with oral health behaviors, perception, knowledge, and dental treatment related outcomes: a systematic review and meta‐analysis

Abstract: The current scientific evidence suggests that no association exists between OHL and any of the outcomes investigated. Further prospective studies with a higher methodological quality are necessary to confirm the evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
70
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 36 publications
3
70
1
8
Order By: Relevance
“…In rural Wisconsin adults, low OHL was associated with lower oral health quality of life, as observed in an other study, and seemed to be particularly influential in the context of appropriate dental care utilization in that lower OHL was significantly associated with both fewer visits to the dentist and more emergency/urgent care visits for NTDC. These findings were again consistent with the Sorensen and colleagues conceptual model of health literacy, but they are in contrast to the recent meta‐analysis that concluded no association between low OHL and visits to the dentist . This may be because participants in our study reported on the total number of dentist visits over the previous 5 years, which may have been a more sensitive outcome as compared to the more typical dental utilization metric of having seen a dentist or not in the last year.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In rural Wisconsin adults, low OHL was associated with lower oral health quality of life, as observed in an other study, and seemed to be particularly influential in the context of appropriate dental care utilization in that lower OHL was significantly associated with both fewer visits to the dentist and more emergency/urgent care visits for NTDC. These findings were again consistent with the Sorensen and colleagues conceptual model of health literacy, but they are in contrast to the recent meta‐analysis that concluded no association between low OHL and visits to the dentist . This may be because participants in our study reported on the total number of dentist visits over the previous 5 years, which may have been a more sensitive outcome as compared to the more typical dental utilization metric of having seen a dentist or not in the last year.…”
Section: Discussionsupporting
confidence: 88%
“…These findings were again consistent with the Sorensen and colleagues conceptual model of health literacy, 26 but they are in contrast to the recent meta-analysis that concluded no association between low OHL and visits to the dentist. 21 This may be because participants in our study reported on the total number of dentist visits over the previous 5 years, which may have been a more sensitive outcome as compared to the more typical dental utilization metric of having seen a dentist or not in the last year. Only 1 other study has examined the association between OHL and emergency NTDC visits (conducted in a sample of Brazilian adults), 22 and our findings are similar to theirs, which relied on self-reported dental emergency visits.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The strengths of this research include the use of a validated instrument to measure wider aspects of OHL, such as the ability to obtain, understand, and utilize oral health information and services to make appropriate oral health-related decisions. Previous studies that have investigated associations between OHL and the same outcomes have used word-recognition instruments (15)(16)(27)(28)(29)(30)(31)(32). Finally, unlike most studies in this field, which have been conducted in developed countries (15), the present study was conducted in a developing country, bringing new evidence to the body of OHL research.…”
Section: Discussionmentioning
confidence: 99%